Field trips in the initial training of teachers: a study in the Colombia center (Encuentros, 2022)
The study analyzes Field Practices in teacher training and their relationship with Professional Knowledge. A process of identification and representation of the content of questionnaires and interviews was carried out based on outputs carried out in a teacher training program. Categories such as TheoryPractice Relationship; Planning; Contribution to teacher training and Difficulties. The results reveal the conceptual strengthening of the practice to subjects of the subjects, and lack of participation of the future teachers in the planning of the exit; aspect, which indicates the need to favor Practices developed from an Investigative perspective. Student perceptions suggest the importance of evaluating practice work during the tour, not just the final product.